Production of lactic acid from pasta wastes using a biorefinery approach - Cristina Marzo-Gago; Joachim Venus; José Pablo López-Gómez (Biotechnology for Biofuels and Bioproducts, 2022)
Abstract A total of 398 kt of pasta waste (PW), generated during the production process of pasta, were produced in 2021. Due to its chemical composition and practically zero cost, PW has already been studied as a raw material for the production of lactic acid (LA) through fermentations. The main objective of this article was to improve the economic viability of the process by replacing commercial enzymes, necessary for starch hydrolysis in PW, with raw enzymes also produced from wastes. Enzyme synthesis was achieved through solid-state fermentation (SsF) of wheat bran by Aspergillus awamori or Aspergillus oryzae at various moisture contents. The maximum amylase activity (52 U/g dry solid) was achieved after 2 days of fermentation with A. awamori at 60% of moisture content. After that, the enzymes were used to hydrolyse PW, reaching 76 g/L of total sugars, 65 g/L of glucose and a yield of 0.72 gglu/gds with the enzymes produced by A. awamori. Subsequently, the hydrolysate was fermented into LA using Bacillus coagulans A559, yielding 52 g/L and 49 g/L with and without yeast extract, respectively. Remarkably, compared to the process with commercial enzymes, a higher LA yield was reached when enzymes produced by SsF were added (0.80 gLA/gglu). Furthermore, the productivities between the two processes were similar (around 3.9 g/L/h) which highlights that yeast extract is not necessary when using enzymes produced by SsF.